2008
DOI: 10.1007/s10637-008-9162-z
|View full text |Cite
|
Sign up to set email alerts
|

Bowel perforation in non-small cell lung cancer after bevacizumab therapy

Abstract: Gastrointestinal perforation is a known adverse event of bevacizumab therapy which so far has occurred only in patients with predisposing risk factors. Our patient illustrates that there must always remain a high index of suspicion regarding bowel perforation in patients developing acute abdominal pain under bevacizumab therapy, even if they have no apparent risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Otherwise, prednisolone or CPS, both of which were taken long-term by this patient, might cause bowel damage. Schellhaas et al (16) reported that diffuse thrombus formation led to perforation of the normal colon, but the present case exhibited diffuse mucosal damage without thrombus. Taken together, it would be more convincing to assume that bevacizumab and/or 5-FU are related to this extensive bowel necrosis.…”
Section: Discussioncontrasting
confidence: 58%
“…Otherwise, prednisolone or CPS, both of which were taken long-term by this patient, might cause bowel damage. Schellhaas et al (16) reported that diffuse thrombus formation led to perforation of the normal colon, but the present case exhibited diffuse mucosal damage without thrombus. Taken together, it would be more convincing to assume that bevacizumab and/or 5-FU are related to this extensive bowel necrosis.…”
Section: Discussioncontrasting
confidence: 58%
“…29, 44 A limitation of the current study is our inability to examine GI wall involvement by tumor prospectively because no reliable methods of diagnosis or documentation have been established. Another possibility is that bevacizumab could limit the blood flow to the splanchnic microvasculature via thrombosis or vasoconstriction, 45,46 leading to GI ischemia, but evidence for this hypothesis is limited.…”
Section: Wwwjcoorgmentioning
confidence: 99%
“…Causes of bleeding include chemotherapy-induced ischaemia (particularly induced by taxanes13 37 and bevacizumab38), infections (particularly CMV and Candida), graft versus host disease (which can occur after stem cell transplantation when the newly transplanted material attacks the transplant recipient's body), autoimmune colitis after treatment with ipilimumab,11 acute radiotherapy-induced ulceration, drug-or radiotherapy-induced inflammatory bowel disease, neutropenic enterocolitis and oxaliplatin-induced portal hypertension 39. Patients should be managed like any other high-risk GI bleed.…”
Section: Gi Symptoms: the Acute Syndromesmentioning
confidence: 99%